Implementation of the Problem-Solving Learning Model in Improving Student Learning Outcomes on Chemical Equilibrium Matter at Senior High School - Renda Suri Pratimi; Wendi Ariful Syafii (Saniya Institute, 2023)
This research focuses on students' difficulties in understanding complex chemical equilibrium material. The aim of this research is to examine the impact of the problem-solving learning model on student learning outcomes at MA YADARO Moyot Sakra East Lombok. The method used is quantitative research with a quasi-experimental design and data analysis through a one-way ANOVA test. The research results show that the problem-solving learning model has a positive impact on learning outcomes, increases students' understanding in solving chemical equilibrium problems, and functions as an effective alternative to increase students' interest in learning. The implications of this research show that applying this model can increase the effectiveness of learning on abstract material.